2016
DOI: 10.1111/bcpt.12587
|View full text |Cite
|
Sign up to set email alerts
|

Bis‐(2‐ethylhexyl) Phthalate Increases Insulin Expression and Lipid Levels in Drosophila melanogaster

Abstract: Bis-(2-ethylhexyl) phthalate (DEHP) is one of the most widely used plasticizers, and human beings are exposed to DEHP via polyvinyl chloride (PVC) materials, medical equipment and even drinking water. While DEHP has been implicated to influence metabolism and endocrine functions, important questions remain about the molecular mechanisms of these effects. We employed the model organism Drosophila melanogaster and examined physiological, molecular and behavioural effects from DEHP-contaminated food. We found tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…diversicolor , DBP affects oxidative stress, lipid and energy metabolism, and osmoregulation 17 . In other invertebrates, including Chironomus riparius 42 , Drosophila melanogaster 43 , and Caenorhabditis elegans 15 , phthalates alter endocrine pathways. The changes affect the ecdysone response as well as the expression of insulin-like peptide.…”
Section: Discussionmentioning
confidence: 99%
“…diversicolor , DBP affects oxidative stress, lipid and energy metabolism, and osmoregulation 17 . In other invertebrates, including Chironomus riparius 42 , Drosophila melanogaster 43 , and Caenorhabditis elegans 15 , phthalates alter endocrine pathways. The changes affect the ecdysone response as well as the expression of insulin-like peptide.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted July 22, 2021. ; https://doi.org/10.1101/2021.07. 19.21260700 doi: medRxiv preprint Our previous research in the Puerto Rico PROTECT birth cohort found associations between prenatal phthalate urine metabolite levels and increased odds of preterm birth [28,29]. In the PROTECT cohort, we also assessed the relationship between maternal lipidomic profiles and adverse birth outcomes and observed numerous significant lipid signatures for spontaneous preterm birth [30].…”
Section: Introductionmentioning
confidence: 93%
“…One of the proposed mechanisms of action and pathways involved in early life phthalateinduced adverse effects is disruption of lipids. Animal studies suggest that phthalates influence circulating lipid levels and lipid signaling [17][18][19][20], by interfering with peroxisome-proliferator active receptor gamma (PPARγ) [21,22]. This points to the possibility that a similar mechanism is at play for humans.…”
Section: Introductionmentioning
confidence: 99%
“…DEHP dealing with possibly upsets sugar homeostasis and starts a diabeteslike metabolic brokenness (Coa et al, 2016). DBP effects insulin and make disturbance in male flies, by managing quality includes in lipid, glucose and xenobiotic digestion (Williams et al, 2016). DBP influence formative time and cause diminishes in the quantity of posterity in D. melanogaster (Atli, Emel, 2010).…”
Section: Micro and Nano Plasticmentioning
confidence: 99%